Situación epidemiológica actual de la triquinosis en Chile. 1991-2000 - Schenone F,Hugo (Sociedad Médica de Santiago, 2002)
Background: Human and animal trichinosis has been recorded in Chile since the late XIX century and is irregularly distributed along the country. From high rates of infection in the early 1900, the frequency of this parasitosis in man has progressively decreased. Aim: To describe and discuss the epidemiological situation of trichinosis in Chile during the decade 1991 - 2000. Material and methods: Human infection was assessed using annual incidence and lethality reports provided by the Ministry of Health, periodic photostrichinoscopies in corpses of non selected individuals autopsied at the Medico Legal Service and periodic national serologic surveys. The advise of one of the authors in an epidemic that occurred in 1999 in the VIII Region was also used. Animal infection was assessed using the annual prevalence of infection in pigs slaughtered in abattoirs, furnished by the Ministry of Health. Results: A total of 631 clinical cases with 4 deaths (0.6%) was recorded. A decline in the incidence, from 0.7 x 100,000 in 1991 to 0.2 x 100,000 in 2000 was recorded. The higher frequency of the parasitosis was observed in the Metropolitan, VI, VIII and X regions. Although human trichinosis has been observed in all seasons, its frequency increases in close relation with the higher pork consumption in cold seasons (45.8% in winter and 37.5% in spring). There has been a decrease of infection rates in pigs from 0.17%o in 1991 to 0.04%o in 1998 - 2000. Conclusions: The incidence and prevalence of trichinosis shows a constant decline in Chile. Considering the geographical characteristics of Chile, it is possible that an undetermined number of pigs are home reared and butchered without veterinary control, constituting an important source of human trichinosis (Rev Méd Chile 2002; 130: 281-5